Continue Use Intention Analysis Using The Integration of The Unified Theory of Acceptance and Use of Technology (UTAUT) 2 and Delone & Mclean (D&M) Models Modified in The My TelU Mobile Student Account Application - Darmawan, Singgih; Rina Djunita Pasaribu, Rina Djunita (International Journal of Science, Technology & Management, 2024)
My TelU Mobile is a learning support application released by Telkom University on May 25, 2021. This application can be downloaded on the Play Store and App Store and has become a super app that has quite a high number of downloads. However, its user traffic is not yet stable, as seen in the decreasing usage traffic during the lecture period. The purpose of this study was to determine the factors that influence the acceptance and use of the My TelU Mobile application using an integration of the UTAUT-2 and Delone & McLean models. This study uses a quantitative method with descriptive and causal research types. The sampling technique uses a non-probability sampling technique of the purposive sampling type with a sample size of 400 respondents. The data analysis technique uses descriptive analysis and PLS. The findings of this study are that effort expectancy, information quality, service quality, user satisfaction have a significant effect on continue use intention and system quality, information quality, service quality have a significant effect on user satisfaction. However, performance expectancy, social influence, facilitating condition, habit, hedonic motivation, and system quality do not have a significant effect on continue use intention of My TelU Mobile application.